Emerging role of C5aR2: novel insights into the regulation of uterine immune cells during pregnancy - Froehlich, Fenna; Landerholm, Konstanze; Neeb, Johanna; Meß, Ann-Kathrin; Seiler, Daniel Leonard; Tilburgs, Tamara; Karsten, Christian Marcel (Frontiers in Immunology, 2024)
Pregnancy is a fascinating immunological phenomenon because it allows allogeneic fetal and placental tissues to survive inside the mother. As a component of innate immunity with high inflammatory potential, the complement system must be tightly regulated during pregnancy. Dysregulation of the complement system plays a role in pregnancy complications including pre-eclampsia and intrauterine growth restriction. Complement components are also used as biomarkers for pregnancy complications. However, the mechanisms of detrimental role of complement in pregnancy is poorly understood. C5a is the most potent anaphylatoxin and generates multiple immune reactions via two transmembrane receptors, C5aR1 and C5aR2. C5aR1 is pro-inflammatory, but the role of C5aR2 remains largely elusive. Interestingly, murine NK cells have been shown to express C5aR2 without the usual coexpression of C5aR1. Furthermore, C5aR2 appears to regulate IFN-γ production by NK cells in vitro. As IFN-γ produced by uterine NK cells is one of the major factors for the successful development of a vital pregnancy, we investigated the role anaphylatoxin C5a and its receptors in the establishment of pregnancy and the regulation of uterine NK cells by examinations of murine C5ar2 -/-pregnancies and human placental samples. C5ar2 -/-mice have significantly reduced numbers of implantation sites and a maternal C5aR2 deficiency results in increased IL-12, IL-18 and IFN-γ mRNA expression as well as reduced uNK cell infiltration at the maternal-fetal interface. Human decidual leukocytes have similar C5a receptor expression patterns showing clinical relevance. In conclusion, this study identifies C5aR2 as a key contributor to dNK infiltration and pregnancy success.